The story of human language - McWhorter, John H.; Teaching Company (Chantilly, VA : Teaching Company, 2004)
Language is fascinating. It defines humans as a species, placing us head and shoulders above even the most proficient animal communicators. Professor McWhorter explores many of the common questions about language, such as: Why isn't there just a single language? Or, How does a language change, and when it does, is that change indicative of decay or growth? In short, everything about a language is eternally and inherently changeable, from its word order and grammar to the very sound and meaning of basic words, while word histories reveal the phenomena of language change and mixture worldwide.
Part 3 : Lecture 25. A new perspective on the story of English -- Lecture 26. Does culture drive language change? -- Lecture 27. Language starts over: Pidgins -- Lecture 28. Language starts over: Creoles I -- Lecture 29. Language starts over: Creoles II -- Lecture 30. Language starts over: signs of the new -- Lecture 31. Language starts over: the Creole continuum -- Lecture 32. What is Black English? -- Lecture 33. Language death: the problem -- Lecture 34. Language death: prognosis -- Lecture 35. Artificial languages -- Lecture 36. Finale: master class.
DVD.
Thirty-six lectures of thirty minutes each by lecturer Professor John McWhorter, Senior Fellow at the Manhattan Institute.
Producer, James Blandford ; director, Jon Leven ; academic content supervisor, Pam Greer ; camera, Tom Dooley, Jim Allen, Amanda Carter.
Course guidebooks include lecture outline, timeline, glossary, and bibliography.
Keywords: Linguistics; Historical linguistics; Linguistic analysis (Linguistics); Sociolinguistics; Psycholinguistics; Linguistics -- History; Linguistics -- Study and teaching; Pidgin languages; Creole dialects; Dialectology; Languages, Artificial; Language and languages -- Philosophy -- History